2015
DOI: 10.1063/1.4919442
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mechanism study of cerium oxide based random access memories

Abstract: Performance stability and functional reliability in bipolar resistive switching of bilayer ceria based resistive random access memory devices Dual operation characteristics of resistance random access memory in indium-gallium-zinc-oxide thin film transistors Appl. Phys. Lett.Electrical characteristics and carrier transport mechanisms of write-once-read-many-times memory elements based on graphene oxide diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 26 publications
(28 reference statements)
2
32
0
Order By: Relevance
“…Between late 1990 and early 2000, on account of the detection of hysteresis Current-Voltage (I-V) characteristics in oxides with perovskite structure, a great number of works concerning resistive switching (RS) memory based on oxide materials was done. [125,126] Especially, the binary metal oxides attracted great attentions, since they possess extremely simple compositions than perovskite oxides and display excellent resistive switching performance under polycrystalline states. For example, lowtemperature grown or solution-processed TiO 2 , [127,128] Al 2 O 3 thin film, [129,130] as well as CeO x [131] have been investigated.…”
Section: Metal Oxidementioning
confidence: 99%
“…Between late 1990 and early 2000, on account of the detection of hysteresis Current-Voltage (I-V) characteristics in oxides with perovskite structure, a great number of works concerning resistive switching (RS) memory based on oxide materials was done. [125,126] Especially, the binary metal oxides attracted great attentions, since they possess extremely simple compositions than perovskite oxides and display excellent resistive switching performance under polycrystalline states. For example, lowtemperature grown or solution-processed TiO 2 , [127,128] Al 2 O 3 thin film, [129,130] as well as CeO x [131] have been investigated.…”
Section: Metal Oxidementioning
confidence: 99%
“…The presence of rich oxygen vacancies in CeO 2 endows it with exceptional oxygen storage and release capabilities. For these reasons, recent years have witnessed a surge of research pertaining to using CeO 2 as an insulating layer for memristive systems . For instances, Hsieh et al reported RRAM in Al/CeO x /Au with a low operating voltage and high resistance ratio, Kim fabricated Pt/CeO 2 /Pt device with resistance change >10 5 fold that mimics biological synaptic behaviors.…”
Section: Formation Energies (Eform) Of Polaron In Ceo2 In Presence Ofmentioning
confidence: 99%
“…Furthermore, the hardware integration of synaptic connections in advanced neural networks requires memristors with multiple resistive states [12,13]. These are challenging requirements and are difficult to implement without significant innovations.The phenomenological principle of memristor device operation is based on the change in the physical properties of a conductive filament (associated with the presence of oxygen vacancies) by applying an electric field across the metal oxide switching layer [14][15][16]. The resulting motion of the oxygen vacancies alters the device resistance between low (Set) and high (Reset) states, depending on the direction and the amplitude of the electric field.…”
mentioning
confidence: 99%
“…The phenomenological principle of memristor device operation is based on the change in the physical properties of a conductive filament (associated with the presence of oxygen vacancies) by applying an electric field across the metal oxide switching layer [14][15][16]. The resulting motion of the oxygen vacancies alters the device resistance between low (Set) and high (Reset) states, depending on the direction and the amplitude of the electric field.…”
mentioning
confidence: 99%